Wideband Audio Source Localization using Microphone Array and MUSIC Algorithm - Anshul Kant Saxena (2009)
In this project a DSP based real time system has been developed to localize the audio source in reverberant environment. The System is developed on TI’s TMS320C6713 DSP. The Incoherent Wideband MUSIC Algorithm used in the project is based on Eigenvalue decomposition method. The algorithm is simulated in MATLAB under real time constraint. The project is developed in C using TI’s Code Composer Studio.
Keywords: Breitbandsignal; Microphone Array Verarbeitung